The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s12519-023-00698-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of hypoxic–ischemic encephalopathy: a systematic review

Abstract: Background Current diagnostic criteria for hypoxic–ischemic encephalopathy in the early hours lack objective measurement tools. Therefore, this systematic review aims to identify putative molecules that can be used in diagnosis in daily clinical practice (PROSPERO ID: CRD42021272610). Data sources Searches were performed in PubMed, Web of Science, and Science Direct databases until November 2020. English original papers analyzing samples from newborns >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
(105 reference statements)
1
6
0
1
Order By: Relevance
“…Numerous plasma biomarkers have been investigated to monitor the clinical progression of HIE ( Caramelo et al, 2023 ). Currently, the IgG N-glycan assay offers a new diagnostic approach for inflammatory and immune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous plasma biomarkers have been investigated to monitor the clinical progression of HIE ( Caramelo et al, 2023 ). Currently, the IgG N-glycan assay offers a new diagnostic approach for inflammatory and immune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Atualmente, a HT é o tratamento padrão para casos moderados a graves de EHI, consistindo no resfriamento da temperatura corporal total do recém-nascido (mantendo-a entre 32°C e 34°C) ou seletivamente da cabeça por até 72 horas. Esta abordagem visa retardar a taxa metabólica e o acúmulo de citocinas inflamatórias, diminuindo a ativação de vias intracelulares que levam à morte celular programada (Figueiredo et al, 2021;Caramelo et al, 2023;Puga et al, 2023).…”
Section: • Introduçãounclassified
“…Recent evidence has shown that serum biomarkers like calcium-binding protein B can indicate early-stage HIE and are related to the onset and development of brain injury (6). In addition, soluble lectin-like oxidized low-density lipoprotein receptor-1 (sLOX-1) can reflect the body's vascular endothelial injury and inflammatory reaction to a certain extent and is a biomarker for a variety of ischemic cardio-cerebrovascular diseases such as acute coronary syndrome and acute cerebral infarction; however, its relationship with hypoxia and ischemia-induced HIE remains unclear (7,8).…”
Section: Introductionmentioning
confidence: 99%